Open versus laparoscopic colectomy - which is better from immunity-point of view: three-year single-center retrospective study - Hussein, Tawfik A. T.; Ajawi, Ahmad M. (International Surgery Journal, 2024)
Background: Objective of the study was evaluation of the impact of colorectal surgery on patients’ immune milieu through comparison of outcomes of patients had open colectomy (OC) versus laparoscopic colectomy (LC) for colorectal carcinoma (CRC). Methods: The design of the study was retrospective observational study. The study setting was Mediclinic Airport Road Hospital, Abu Dhabi, UAE. Files of CRC patients who had LC (group-LC) or OC (group-OC) were revised for perioperative data and estimated serum inflammatory cytokines’ levels. Statistical analyses of the relation between the postoperative (PO) outcomes and serum cytokines’ levels estimated in samples obtained immediately PO. Results: Patients underwent LC had significantly lower amount of operative bleeding and shorter operative time with lower frequency of patients required ICU and shorter duration of ICU stay. LC provided lower pain scores with shorter duration till 1st ambulation and passage of flatus and shorter duration of hospital stay. LC significantly reduced serum cytokines’ levels in immediate PO samples of LC than OC patients. At 1-week PO, serum cytokines’ levels were significantly lower than in immediate PO samples with significant difference between LC and OC samples. Moreover, epidural anesthesia (EA) and opioid-free general anesthesia (GA) had lower serum cytokines’ levels than opioid-based GA. Statistical analyses defined laparoscopic surgery under EA and non-opioid analgesia as the highly significant predictor for favorable PO surgical outcomes and proper control on surgical immune response. Conclusions: LC significantly improved PO surgical outcomes and attenuated the surgical immune response with significant difference than OC. EA juxtaposed with opioid-free analgesia significantly provided further control on the surgical immune response.